2021
DOI: 10.21037/apm-20-2507
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic factors of apical periodontitis by root canal treatment and endodontic microsurgery-a retrospective cohort study

Abstract: Background: The aim of this study was to analyze the outcome and prognostic factors of root canal treatment (RCT) and endodontic microsurgery (EMS) in the treatment of apical periodontitis (AP), respectively, and to compare the outcome and prognostic factors between initial RCT and nonsurgical retreatment (re-RCT) for AP.Methods: Patients with AP were recruited from the Stomatology Department of Peking University Third Hospital from January 2016 to December 2019. Data were collected by medical records review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…The impact of operator skill level and associated variations in technical quality was partly overcome in the present study by supervision and hands‐on guidance by experienced endodontist, but the inherent variation amongst graduate students' performance should be recognized. Our findings of no association of outcome after surgery with registered parameters agrees well with recent results (Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…The impact of operator skill level and associated variations in technical quality was partly overcome in the present study by supervision and hands‐on guidance by experienced endodontist, but the inherent variation amongst graduate students' performance should be recognized. Our findings of no association of outcome after surgery with registered parameters agrees well with recent results (Liu et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…An increase in 1 mm 3 in the initial volume of a periapical lesions increased the healing time by 0.3%. Liu et al (2021) analysed the prognostic factors of root canal treatment and nonsurgical retreatment for teeth with apical periodontitis. They observed that a statistically significant preoperative prognostic factor in the successful healing rate was the patient's age (p < .05).…”
Section: Discussionmentioning
confidence: 99%
“…They observed that a statistically significant preoperative prognostic factor in the successful healing rate was the patient's age ( p < .05). Younger patients had a more favourable outcome (Liu et al., 2021). Other authors disagree with this finding, for example, Saini et al., 2023 concluded that age was not a prognostic factor for the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to a case deemed "successful," there is an even wider heterogeneity recorded in the literature. According to the consensus Despite the fact that some investigators conformed to the aforementioned guidelines (Krell & Caplan, 2018;Malentacca et al, 2021) others evaluated success only by disappearance of symptoms (Kim et al, 2013;Lee et al, 2021b) and reduction in the size of the periapical lesion (Liu et al, 2021). On the contrary, a broader range of prerequisites for success was implemented by other research teams, which further considered no increase in crack-associated periodontal probing (Davis & Shariff, 2019;de Toubes et al, 2022), periapical index (PAI) score ≤2 (de Toubes Dow, 2016), no increase in crestal bone loss, no sensitivity in percussion, palpation or bite test, as well as the presence of an occlusally, equilibrated full-coverage restoration (Davis & Shariff, 2019).…”
Section: Success Ratesmentioning
confidence: 99%
“…On the contrary, a broader range of prerequisites for success was implemented by other research teams, which further considered no increase in crack‐associated periodontal probing (Davis & Shariff, 2019 ; de Toubes et al, 2022 ), periapical index (PAI) score ≤2 (de Toubes et al, 2022 ; Dow, 2016 ), no increase in crestal bone loss, no sensitivity in percussion, palpation or bite test, as well as the presence of an occlusally, equilibrated full‐coverage restoration (Davis & Shariff, 2019 ). Respectively, two studies recorded as “failures” cases with an unchanged periapical lesion, although they were followed up for a mean period of 19 months (Liu et al, 2021 ) and 23.3 months (Chen et al, 2021 ), instead of the proposed 4‐year time span (Endodontology, 2006 ). In addition, other studies (Lee et al, 2021b ; Lu et al, 2021 ) had a shorter follow‐up than the minimum required (1 year) for the assessment of success (Endodontology, 2006 ).…”
Section: Outcomes Of Endodontically Treated Cracked Teethmentioning
confidence: 99%